Scaling of the fracture toughness of freestanding metallic thin films with the yield strength. Issue 10 (3rd October 2018) - Preiß, Eva I.; Gannott, Florentina; Göken, Mathias; Merle, Benoit
ABSTRACT: The influence of the yield strength on the fracture toughness of freestanding metallic films with a thickness of ∼150 nm was investigated by bulge testing. For this purpose, gold films prepared by thermal evaporation were tested at room temperature and at 100°C. Additionally, different Au-Ag solid-solution strengthened films were studied. The fracture toughness of the films is observed to increase with increasing yield stress. This is at first sight counterintuitive but can be explained by previously observed severe necking leading to a chisel-point type of fracture in freestanding metallic thin films. GRAPHICAL ABSTRACT: IMPACT STATEMENT: Freestanding metallic thin films exhibit an extremely low fracture toughness. It is shown in this publication that KIC can be significantly improved by increasing the yield strength of the films.